If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 13 = 68 + -1x Reorder the terms: 13 + 10x = 68 + -1x Solving 13 + 10x = 68 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 13 + 10x + x = 68 + -1x + x Combine like terms: 10x + x = 11x 13 + 11x = 68 + -1x + x Combine like terms: -1x + x = 0 13 + 11x = 68 + 0 13 + 11x = 68 Add '-13' to each side of the equation. 13 + -13 + 11x = 68 + -13 Combine like terms: 13 + -13 = 0 0 + 11x = 68 + -13 11x = 68 + -13 Combine like terms: 68 + -13 = 55 11x = 55 Divide each side by '11'. x = 5 Simplifying x = 5
| 9y^2-12y+1=0 | | 3x+8=2x+20 | | 7(3x+4)=9x-12-x | | 2x+3+4x+2=11 | | 13x-(25+11x)=165-2(4x+10) | | 16x^2-13x=0 | | 5x+37=179 | | 12-3(2x+9)=15 | | 3(6z-1)-4(z+2)=5(z+1) | | 4d+3=8 | | 7x+4x=12 | | -9x-1=71 | | 7x+4+=12 | | 217-5x=40x+22 | | 10-7x=127-28x | | 10-7x=127-18x | | 114-5x=2x+26 | | -8x-5=19 | | 5x^2+3x=3 | | 5y-2x=10 | | 0.04(x-0.2)=-0.03(2x+0.6) | | .167x^2-.333x-1=0 | | 9x+5=2x+33 | | 25-x^2= | | 8x-2x+18=0 | | (1+7i)+(9-1)=0 | | 0.3(c+5)=0.4(1-2c) | | r^2+5=0 | | r^2+1=0 | | x/(x-3)+3=5x/(3-x) | | 2(x-0.2)=3x-1.4 | | 3R+5-R= |